1995
DOI: 10.1246/bcsj.68.2955
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activities of Dihydric Phenol Derivatives for the Autoxidation of Tetralin

Abstract: The antioxidant activities of dihydric phenols, such as catechol, resorcinol, and hydroquinone, and their twenty-three alkyl and benzyl substituted derivatives were evaluated by means of an oxygen-absorption method at 60 °C for determining the oxidation of tetralin. Catechols exhibited a much higher stoichiometric factor (2.0—2.3) compared with those of other compounds. The stoichiometric factors of hydroquinones (0.6—1.1) are almost half those of catechols, and are lower for the resorcinols (0.3—0.6). In addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Yamamura and coworkers used an oxygen absorption method to study the effects of a series of 46 dihydric phenols on inhibition of azo-initiated oxidation of tetralin 160 . They reported activities in terms of the stoichiometric factor, n, and the rate of oxygen absorption, R inh , during induction periods.…”
Section: Dihydroxy Phenols: Catechols and 14-hydroquinones-intramolementioning
confidence: 99%
See 1 more Smart Citation
“…Yamamura and coworkers used an oxygen absorption method to study the effects of a series of 46 dihydric phenols on inhibition of azo-initiated oxidation of tetralin 160 . They reported activities in terms of the stoichiometric factor, n, and the rate of oxygen absorption, R inh , during induction periods.…”
Section: Dihydroxy Phenols: Catechols and 14-hydroquinones-intramolementioning
confidence: 99%
“…The antioxidant properties of 1,4-hydroquinones has been reexamined by several groups more recently. Yamamura and coworkers 160 found that these hydroquinones were less effective in reducing oxygen uptake than catechols (by about one-half) and the stoichiometric factors of hydroquinones ranged (0.6-1.1) to about half that of the catechols. It is interesting to note that they attributed the higher activity of catechols, compared to hydroquinones, to the increased stability of the derived phenoxyl radicals due to the intramolecular hydrogen bond.…”
Section: Dihydroxy Phenols: Catechols and 14-hydroquinones-intramolementioning
confidence: 99%
“…OH HO 1 H NMR (400 MHz, DMSO-d6) δ = 9.14 (s, 1H), 9.00 (s, 1H), 7.22 (q, J=7.4, 4H), 7.11 (t, J=6.7, 1H), 6.86 (d, J=8.4, 1H), 6.25 (s, 1H), 6.18 (d, J=8.4, 1H), 4.32 (q, J=7.2, 1H), 1.45 (d, J=7.2, 3H). 13 C NMR (100 MHz, DMSO-d6) δ =156.22, 155.10, 147.12, 127.…”
mentioning
confidence: 99%
“…13 C NMR (100 MHz, DMSO-d6) δ =156.22, 155.10, 147.12, 127. 96 1 H NMR (400 MHz, DMSO-d6) δ = 8.94 (s, 2H), 7.17 (m, 10H), 6.88 (d, J=4.9, 1H), 6.27 (s, 1H), 4.29 (q, J=7.2, 2H), 1.44 (m, 6H). 13 C NMR (100 MHz, DMSO-d6) δ =153.…”
mentioning
confidence: 99%
“…Many functionalized hydroxyquinones are of interest because of their applications as antioxidants. 59 Hence their synthesis has received considerable attention. One of the earliest methods developed for their synthesis is the Thiele-Winter acetoxylation, which utilizes sulfuric acid as a catalyst.…”
Section: Bismuth Triflate Catalyzed Acylation Of P-quinonesmentioning
confidence: 99%